Analysis Of Hospital Management Performance Standards With Implementation Of Comprehensive Neonatal Obstetric Services (CNEOS) At Royal Prima Medan General Hospital In 2022 - Akbar Dinur, Rakhmat; Kaban, Karmila; Lestari Ramadhani, Sri; Isabella Silalahi, Marlinang (International Journal of Health and Pharmaceutical (IJHP), 2022)
From the Indonesian Demographic and Health Survey (IDHS) in 2012, maternal and infant mortality rates in Indonesia continue to increase. Comprehensive Neonatal Emergency Obstetric Service (CNEOS) is a comprehensive service effort in hospitals to deal with obstetric and neonatal emergency cases whose activities in addition to being able to carry out all Basic Neonatal Emergency Obstetric Services (BNEOS) must also be able to provide blood transfusions and Caesarean sections as well as intensive neonatal care. , where this activity is very important considering the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are still high. The purpose of the study was to determine the Analysis of Hospital Management Performance Standards with the Implementation of Comprehensive Emergency Neonatal Obstetrics Services (CNEOS) at the Royal Prima General Hospital Medan in 2022. The results showed that there was a relationship between human resources, completeness of facilities and infrastructure, and management with the implementation of CNEOS. at the Royal Prima General Hospital Medan in 2022. However, there is no relationship between the availability of drugs and supporting information systems with the implementation of CNEOS at the Royal Prima Medan General Hospital in 2022.